Transforming Interest in Arabic Language Learning: An Analysis of the Edu-humorous Video meme trend on Instagram as an innovative pedagogical solution - Muhammad Ari Nurrohman; Mahbub (IDEAS: Journal on English Language Teaching and Learning, Linguistics and Literature, 2026)
This study is motivated by the low level of students’ interest in learning Arabic, which is often perceived as a difficult and less engaging subject amid the rapid development of digital culture. The aim of this research is to analyze the role of educational–humorous meme videos on the Instagram account @qawla.id in increasing students’ interest in learning Arabic and in shaping a new, more contextual and adaptive representation of Arabic learning. This research employs a qualitative method with a descriptive approach and was conducted at Madrasah Aliyah Negeri 4 Banyuwangi as the research site. Data collection techniques include classroom observation, in-depth interviews with students and Arabic language teachers, as well as text studies and document analysis of educational–humorous meme video content. Data analysis was carried out through the stages of data reduction, data display, and conclusion drawing in a systematic manner. The results indicate that educational–humorous meme videos are able to increase students’ interest and engagement in learning, reduce anxiety in Arabic language learning, and foster a positive representation of the subject. Furthermore, the use of meme videos encourages a shift in the learning paradigm from teacher-centered to learner-centered and bridges formal classroom learning with students’ digital culture. Therefore, educational–humorous meme videos can be regarded as an innovative pedagogical strategy that is relevant and effective for the development of Arabic language learning in the digital era.